SmartMY - an easy-access medication price checker mobile application prototype - Nik Mustaffa Shapri, Nik Aisyah Najwa; Ibrahim, Nurul Alyaa; Azlan, Saliha (Faculty of Pharmacy, 2025)
The rising cost of generic and brand-name medications have raised concerns about affordability and accessibility. In Malaysia's private healthcare system, individuals may face high out-of-pocket expenses, necessitating a reliable pricing guide. However, noexisting mobile application provides convenient access to medication prices. SmartMY was developed as a user-friendly mobile app to enhance public access to recommended retail medication prices. Built on the AppSheet platform, it integrates retail price data from the Pharmaceutical Services Programme, Ministry of Health (MOH) Malaysia. The application interface was designed to facilitate a pricing search capability using the generic name, brand name, or medication registration number. The information provided includes the retail price per unit and per pack of the medication. The pricing within the application serves as a guide for retail prices. The users may also provide feedback for the continuous improvement of the application. An intuitive mobile application for a medication retail price guide was designed and developed. This application serves as a useful tool for the public to readily access and compare medication prices, promoting transparency and informed decision-making when purchasing medications. With regular updates and user feedback, the application aims to provide accurate and up-to-date information for users seeking affordable healthcare options. In the future, the application seeks to augment its functionality by incorporating a price comparison feature that enables users to compare medication prices from different community pharmacies.